Sanksi Pidana Terhadap Pelaku Tindak Pidana Santet - Rachmad Alif Al Buchori; I Made Sepud; I Made Minggu Widyantara (Warmadewa Press, 2021)
The philosophical background of witchcraft can be classified as a criminal act because witchcraft is recognized and believed to exist in the community, and causes unrest, but cannot be prevented and eradicated through law because of difficulties in proving it. So in this case, criminal sanctions are needed for the perpetrators of witchcraft. The purpose of this study is to analyze the criminal sanctions against the perpetrators of the crime of witchcraft. The method used in this research is normative with a statutory approach. The data sources used are primary, secondary, tertiary data sources obtained from recording and quoting relevant legal materials. The results of the study reveal that accountability for perpetrators of witchcraft is not written or listed in the current Criminal Code (KUHP). But it is different in the Draft Criminal Code (RKUHP), perpetrators of witchcraft can now be made a criminal act even though it does not specifically include the word witchcraft in the RKUHP. The formulation of the crime in Article 293 of the RKUHP is increasingly clear that perpetrators of witchcraft possessing the elements referred to may be subject to a maximum imprisonment of 5 years and a category IV fine.